The Perpetual Catwalk of Modernity: - Kaiser Haq (Crossings)
While lazily channel browsing some years back, my attention was caught by an ongoing discussion on a now defunct Kolkata-based channel. In fact, that particular program is the only one I vividly remember from the short and distinguished life of Tara TV. Several participants had been marshalled to talk about “adhunikata,” modernity. The session was in its final stages, and seemed to have been an informal for-and-against debate. The only speaker I could watch had begun his spiel. I do not remember his name but I was struck by his cheerful countenance, and his engagingly animated and fluent delivery. He was of modest build, which might have been a consequence of a hyperactive metabolism. This is a retrospective observation I make in passing because, if we were to personify “modernity,” one of its conspicuous physical attributes would be a hyperactive metabolism.....